Partisipasi petani ubi kayu (Manihot esculenta) dalam upaya konservasi lahan kering di Kota Pekanbaru - Nazri Zulfajrin; Sukendi Sukendi; Nofrizal Nofrizal (Pelantar Press, 2021)
This research was conducted in September 2020 in Tenayan Raya District, Pekanbaru City. This study describes the participation of cassava farmers in the conservation of dry land according to the Land Conservation Index (IKK) and analyzes socio-economic factors that influence these conservation activities. Respondents in this study were cassava farmers who have farming land over one hectare. Conservation activities carried out by farmers to carry out dry land conservation include, making terraces or uplands and planting in the direction of contour lines or crossing slopes, use of mulch or terrace reinforcing grass, use of manure and construction of drainage channels. The approach used in this study used survey methods and interviews with cassava farmers to obtain farmer socio-economic data, and analyzed using simple regression methods. The results showed that the farmers carried out dry land conservation activities at a moderate level. The influence of socio-economic factors that affect the dry land conservation activities of cassava farmers is the factor of acceptance and land ownership status.